The Pretrial Fairness Act: Equity, but at What Cost? - John Burns (Washington University Journal of Law and Policy, 2025)
This Note traces the evolution of bail from its origins to modern commercial bail, highlighting how the system has disproportionately affected low-income defendants. In 2023, Illinois became the first state to eliminate cash bail with the enactment of the Pretrial Fairness Act, which attempted to remedy longstanding inequities. The Note situates Illinois’s approach between New Jersey’s successful risk-based reform and California’s oversimplified and harmful “zero bail” experiment. While Illinois’s reform represents a meaningful step toward fairness, this Note argues that its reliance on a categorical approach and its limited use of pretrial assessments may unintentionally undermisne its effectiveness. The Note concludes that Illinois must go further by expanding judicial discretion and mandating the use of risk assessment tools.
Keywords: BeyondCashBail; PretrialReform; JusticeNotWealth